Saving Private Ryan - Rodat, Robert; Kahn, Michael; Williams, John; Hanks, Tom; Burns, Edward 1968-; Sizemore, Tom 1961-; Damon, Matt
The story begins with World War II's historic D-Day invasion of Normandy beach. Once the men move beyond the beach, Captain John Miller must take his men behind the German lines to find Private James Ryan, whose three brothers have already been killed in combat. Faced with impossible odds, the men question their orders. Why are eight men risking their lives to save just one? Surrounded by the brutal realities of war, each man searches for his own answer and the strength to triumph over an uncertain future with honor, decency and courage.